Isolation and phytochemical investigation of antioxidative from the curcuma longa leaves / Nurhidayah Osman - Osman, Nurhidayah (Faculty of Applied Sciences, 2017)
Curcuma longa leaves were applied in cosmetics, food additive and medicinal purpose. Curcuma longa leaves contains secondary metabolites of terpenoids which have been found in antioxidant properties. Based on experiments isolated compound from petroleum ether extract done by GCMS found the suggested structure of antioxidative components are Benzene, (2,4cyclopentadien-1-ylidenemethyl), Estra-I ,3,5( I0)-trien-17ᵝ01, Benzene, 1,3-dimethyl, Hexadecanoic acid, methyl ester, IH-Indene, 1methylene, Hexadecanoic acid, 1-(hydroxymethyl)-1,2-ethanediyl ester, Cyclopentanol, I-methyl and Triphenylphosphine oxide. While, scavenging activity of extract Curcuma longa leaves on DPPH radicals IC50 value to perform antioxidant properties, it is showed the dichloromethane has the strongest scavenging activity (IC50 > 6.25 µg / ml) compared with petroleum ether extract (lC50 > 100 µg / ml) and methanol extract (IC50 > 100 µg / ml). As Curcuma longa leaves has antioxidant properties it has potential for the development of modem medicine for the treatment of various diseases.